2017
DOI: 10.1259/bjr.20170213
|View full text |Cite
|
Sign up to set email alerts
|

Predicting poor outcome from simple ankle injuries: a prospective cohort study

Abstract: Medium to long term clinical outcomes were not solely determined by the severity of injury. Some patients with simple injuries were seen to have ongoing problems, whereas some with complex injuries recovered completely in a shorter period. Advances in knowledge: The severity of an ankle injury determined by radiological imaging does not necessarily dictate the severity of a patient's symptoms and the trajectory of their recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It appeared that there was no clinically significant difference in functional outcome based on the types of injury that patients underwent but it was presented that there are factors to consider early in the recovery after an injury to optimise a return to normal function. 10 This study has shown a similar result to a paper comparing ankle ligament injuries detected by ultrasound as compared to MRI. 19 Ultrasound has also been clearly shown to demonstrate soft tissue injuries of the ankle well, although, there is some attention to detail required to identify the ankle ligaments correctly.…”
Section: Bjr Allen Et Alsupporting
confidence: 83%
See 1 more Smart Citation
“…It appeared that there was no clinically significant difference in functional outcome based on the types of injury that patients underwent but it was presented that there are factors to consider early in the recovery after an injury to optimise a return to normal function. 10 This study has shown a similar result to a paper comparing ankle ligament injuries detected by ultrasound as compared to MRI. 19 Ultrasound has also been clearly shown to demonstrate soft tissue injuries of the ankle well, although, there is some attention to detail required to identify the ankle ligaments correctly.…”
Section: Bjr Allen Et Alsupporting
confidence: 83%
“…The functional outcome of the patients from this study measured at 3 and 6 months, and the associations with ligament injury patterns has already been presented. 10 Therefore, the objectives of this paper are to describe the study in total but to focus on examining the occult fracture incidence and associations, and to also consider the appropriateness of examination methods for acute ankle injuries.…”
mentioning
confidence: 99%
“…Conversely, the SLL test conducted in this study focused on the ankle joint function required for acquiring movement, difficulty in standing, standing, heel raising, and hopping. Bullock et al have investigated functional recovery after ankle trauma and used the same evaluation items as those used in this study [23], suggesting that these items are appropriate for evaluating ankle function. Additionally, this test can be performed anywhere, and the stress experienced in the varus/valgus and internal/external rotational directions is less; therefore, it can be performed according to the ATFL injury severity in the acute phase.…”
Section: Discussionmentioning
confidence: 99%